2011
DOI: 10.1007/s10903-011-9499-9
|View full text |Cite
|
Sign up to set email alerts
|

Social Support Modifies the Association Between Household Food Insecurity and Depression Among Latinos with Uncontrolled Type 2 Diabetes

Abstract: Prevalence of depression is high among individuals with type 2 diabetes (T2D). The objective of the current study was to identify the socio-demographic, psychosocial, cultural, and clinical risk factors that predispose to depression, and resources that protect from depression among low income Latinos with T2D. Participants (N = 211) were interviewed in their homes upon enrollment. Multivariate logistic regression was used to identify factors associated with depressive symptoms based on a score of ≥21 on the Ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
47
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 54 publications
(53 citation statements)
references
References 33 publications
6
47
0
Order By: Relevance
“…In agreement with previous studies [1-3], we found that food insecurity was significantly associated with depression in bivariate analyses. Social support was a significant mediator of this relationship.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…In agreement with previous studies [1-3], we found that food insecurity was significantly associated with depression in bivariate analyses. Social support was a significant mediator of this relationship.…”
Section: Discussionsupporting
confidence: 93%
“…A study of depression and food insecurity in a population of Latinos with type 2 diabetes from Hartford, Connecticut found that those with high social support were less likely to become depressed when confronted with food insecurity than those with medium or low social support, suggesting that social support acts modifies the association and acts as a buffer in the association between food insecurity and depression in this population [3]. A buffering effect of social support was also seen among people living with HIV/AIDS in Uganda, such that instrumental social support protected against the depressive effects of food insecurity [1].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Other work has shown that Hispanics may have social networks that can provide resources to buffer the deleterious effects of financial deprivation. 51 …”
Section: Discussionmentioning
confidence: 99%
“…Household food insecurity (HFI) is a major stressor (21) that is associated with depression and diabetes distress (21) and anxiety (22,23). Sleep and wakefulness are disrupted by a variety of factors, including those that are physiologic, behavioral, and environmental (24).…”
Section: Introductionmentioning
confidence: 99%